PENGARUH KUALITAS OBJEK WISATA TERHADAP MINAT BERKUNJUNG WISATAWAN - Lese, Fentizar Welhelmina; Fanggidae, Rolland E; Fanggidae, Apriana H J (GLORY Jurnal Ekonomi dan Ilmu Sosial, 2020)
This research aims to determine the effect of tourist object quality on the interest of tourists visiting the archipelago in the Oesapa Colorful Beach. This research uses the quality of attractions as an independent variable and the interest of visiting tourists as the dependent variable. The research was conducted using a quantitative approach using incidental sampling with a total sample of 96 people. Collecting data in the field using a questionnaire that has been tested for validity and reliability. The analysis technique in this study uses Simple Linear Regression Analysis techniques, Pearson Correlation Coefficient Test (r)Determination Coefficient Test (R2) and Hypothesis Test using t test. Simple Linear Regression Analysis Results produce an equation: Y = 6.199 + 0.265 so that the results of the description show the quality of attractions has a positive effect on tourist visiting interests. Significance value 0,000 <probability 0.05 and tcount 11.812> t table 1.986, the hypothesis is accepted meaning that the quality of tourist objects significantly influences the interest of tourists visiting the archipelago in the Colorful Coast Oesapa. Keywords: Quality of Attraction, Visiting Interest